PENGARUH PENERAPAN MODEL PEMBELAJARAN KOOPERATIF TIPE THINK PAIR SHARE TERHADAP KEMAMPUAN KOMUNIKASI MATEMATIS PESERTA DIDIK KELAS XII MIPA - Putri, Auliya (Jurnal Edukasi dan Penelitian Matematika, 2023)
One thing that helps educators understand students’ abilities in learning mathematics is mathematical communication. However, math communication abilities are lacking among class XII MIPA SMAN 6 Padang students. This study explores how students' mathematical communication abilities are impacted by and developed by the Think-Pair-Share (TPS) cooperative learning approach. With a Randomised Control Group Only Design, a quasi-experimental methodology was used in this investigation.  By gathering samples using standard random sampling techniques, 177 students from class XII at SMAN 6 Padang as the research population. Instruments included maths tests and quizzes. The data analysis gave the t-test a =0.000. P-Value 0.05 or lower rejects H0. Thus, cooperative learning of the TPS kind enhances students' mathematical communication abilities.Keywords– Mathematical Communication Ability, Cooperative Learning, Think-Pair-Share (TPS)